SISTEM INFORMASI PREDIKSI MAHASISWA PUTUS KULIAH MENGGUNAKAN METODE DATA MINING DENGAN ALGORITMA CHAID - Dhila Franzely Dhimas Putra; Yoga Suhanda; Miri Susanti (Fakultas Ilmu Komputer, 2021)
College life cannot be separated from problems faced by students. This problem is one of the obstacles in completing the study. Droped out students are detrimental to higher education institutions because it will reduce the performance index and harm the students themselves. The purpose of the research is to produce a prediction system for students who will drop out of college using data mining by processing data from ITB Swadharma for the period 1992 to 2019 and modeling using the Chaid algorithm, the results are visualized with the tableau application. The results of the study reveal the fact that the study time is the main factor that influences the prediction of dropout students with a chi-square value of 15,714, factor of accreditation status with a chi-square value of 16,874, gender is the factor with a chi-square value of 5.292.